Tea Infusions as a Source of Phenolic Compounds in the Human Diet - Joanna Klepacka (Applied Sciences, 2022)
Phenolic compounds are components with proven beneficial effects on the human body, primarily due to their antioxidant activity. In view of the high consumption of tea and the numerous factors that affect the nutritional value of its infusions, the aim of this study was to identify the effects of tea type and duration of leaf extraction with water on the levels of phenolic compounds and other components that determine biological activity (oxalates, Ca, Na, Cu, and Mn). Based on assays, infusions of red tea prepared for 20 min were found to be the best source of phenolics (202.9 mg/100 mL), whereas the lowest level of these compounds was determined in infusions of black tea extracted from leaves for 30 min (46.9 mg/100 mL). The highest degree of increase in polyphenol content (by approx. 50%) was noted in red and green tea infused for between 10 and 20 min, whereas for black tea, polyphenol levels decreased with time. The biological activity of tea infusions appears to be determined to the greatest extent by the interactions between phenolic compounds and oxalates (r = 0.6209), calcium (r = 0.8516), and sodium (0.8045). A daily intake of three to four mugs (1 L) of tea infusions provides the human body the entire amount of phenolics recommended for health reasons (as regards red tea, this is possible at 1/3 of the volume) and covers the daily requirement for manganese, as well as (partially) copper.